Feminist Movements in Mexico and Their Transformations in the Context of the COVID-19 Pandemic Based on Communicative Practices in Social Network Sites - García González, Lidia Ángeles (2021)
This article is a qualitative study on feminist movements in Mexico and their transformations in the context of the COVID-19 pandemic based on communicative practices in social network sites. Its purpose is to learn about the challenges, changes and communicative strategies employed in the face of the confinement, which limited the use of public space for feminist protest and accompaniment of women victims of violence. It also presents a theoretical discussion on social movements and feminist collective action in the context of the COVID-19 pandemic (Della Porta, 2020b; Pleyers, 2021; Tabbush, 2021). The results show significant changes in their communicative strategies in social network sites and an increase in emotional exhaustion, given the confinement imposed by the health contingency; however, the use of local initiatives shows a hopeful perspective of retaking the streets in the future.